Da cerâmica arqueológica indígena à cerâmica artística contemporânea: uma questão de identidade cultural na formação e ação de professores. - Dutra, Eduardo (2005)
The present research that inserts in the Line of Research: Education and Arts of the Program of the Post-Graduation in Education from Universidade Federal de Santa Maria - UFSM initiates for an inquiry concerning the cultural identity or the perception of its manifestation in the education of the art that, perhaps do not being understood as such, in an extremely devoid region and abandoned, that, distant from great centers, always meets the edges of the interests from state government. This context is configured in the city of Chapecó, situated in the west, about 600 km far from the State capital of the Santa Catarina, and whose demographic formation is deriving by Italian, Germans, Gauchos, Caboclos and Indians and many others immigrants. Currently the migration for this region in search of opportunities, multiplies the population still more. In this context, the local politics that for was excessively worried about the economic development in the search from solutions for the rise of the unemployment and the financial instability seems to be blind for the problematic that is created for the lack of incentive to the culture. Believing that these conquests demand of time, effective and permanent work, having still as support the work of the art-educators in process of initial formation for the Universidade Comunitária Regional de Chapecó - UNOCHAPECÖ, I glimpse as one of the possible ways to be followed, the construction of a solid social base firmed by ethical and critical principles through the education. Thus I think about one practical fomented for the identification of sides that composes the cultural diversity derivative from multiple peoples that form the city of Chapecó and region, in order to create subsidies to the education of the Art. One searched in the Guarani culture a referential regarding to the ceramist activity, in order to unchain education processes that culminate with the understanding of artistic ceramics and others forms of representation in the contemporary art. Thus, it appears the proposal for the practical development of the pedagogical and directed education of the Art, and more specifically that one that it makes through knowledge, techniques and expressions of the ceramics, assuming as main referential to the aboriginal ceramist tradition identified by a long previous period from the contact with the immigrants, it is for not having in the region no one form of artistic expression through the ceramics that can assistant to understanding the problems referring with teach Art.